Strengthening Digital Branding Capacity of Culinary MSMEs in Denpasar through Community-Based Coaching Clinic - Wicaksana, GDA; Pratama, IGY; Ariesta, I Gusti Bagus Bayu Baruna; Suprihatin, Yeni; Putra, I Made Agus Andika; Saputra, Yoga Ramanda (Room of Civil Society Development, 2025)
This study explores the implementation of a coaching clinic designed to strengthen the digital branding capacity of culinary micro, small, and medium enterprises (MSMEs) at Graha Nawasena Denpasar, a community hub for inclusive entrepreneurship. Adopting a qualitative descriptive approach, data were collected through observation, interviews, and literature review, and analyzed using the Miles and Huberman interactive model. The coaching clinic focused on equipping MSMEs particularly those managed by persons with disabilities with practical knowledge in SEO strategies, visual branding, and storytelling for social media platforms. The findings indicate a marked improvement in participants’ confidence, digital literacy, and branding output. Participants were able to enhance their online presence by applying content creation techniques learned during the program. The initiative not only contributed to increasing the market visibility of MSMEs but also fostered a sense of empowerment and inclusion through a participatory, accessible learning environment. The case of Difel Café illustrates how community-based mentoring can lead to impactful and sustainable branding outcomes. This study provides practical insights for future interventions in digital MSME development, particularly in marginalized communities. It underscores the importance of inclusive, context-sensitive training programs in advancing Indonesia’s digital economy through grassroots empowerment.